Elevated plasma lactate level associated with high dose inhaled albuterol therapy in acute severe asthma. Issue 6 (23rd May 2005) - Rodrigo, G J; Rodrigo, C
Abstract : Background: Lactic acidosis is a recognised event in adult patients with status asthmaticus, particularly in the setting of intensive care. However, it has been infrequently studied in patients attending the emergency departments (ED). Methods: We conducted a prospective and descriptive study to assess levels of lactate and effects on bronchodilator response in adult patients with acute severe asthma treated with high doses of albuterol in the ED. In total, 18 subjects (mean (SD) age 42.9 (2.7) years, FEV1 = 32.2 (10.9)% of predicted) who presented to an emergency department were enrolled in the study. All patients were treated with albuterol; four puffs (100 μg/puff) at 10 minute intervals, delivered by a pressurised metered dose inhaler into a spacer device over a 2 hour period. Results: At the end of treatment, mean (SD) plasma lactate level (2.94 (2.1) mmol/l) was significantly higher (p = 0.001) than baseline. Of the 18 patients, nine (50%) showed lactate levels ⩾2.5 mmol/l (four patients presented values >4 mmol/l); these patients had a shorter duration of attack prior to ED presentation (p = 0.01), a higher pretreatment heart rate (p = 0.005), a lower pretreatment SpO2 (p = 0.03), a lower pretreatment PO2 (p = 0.009), a higher pretreatment PCO2, and a lower pretreatment serum potassium (p = 0.005). However, there were no significant differences in the airway response between groups. Conclusions: This study confirmed previous observations that high lactate concentrations can develop during the first hours of inhaled beta agonist treatment. The presence of a previous hyperadrenergic state may predispose to the development of this condition. A significant improvement in lung function was associated with elevated lactate levels.